2021
DOI: 10.21608/auber.2021.78849.1008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Technologically Enhanced Naturally Occurring Radioactive Materials (TE-NORM) In oil and gas industry On Environment

Abstract: Naturally-occurring radioactive material (NORM) is the term used to describe materials containing radionuclides that exist in the natural environment. The radionuclides of interest include long-lived radionuclides such as uranium-238 (238U), uranium-235 (235U) and thorium-232 (232Th) and their radioactive decay products (such as isotopes of radium, radon, polonium, bismuth and lead), and individual long-lived radionuclides such aspotassium-40 (40K), rubidium-87 (87Rb) and indium-115 (115In). The parent radionu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Since the factors that cause the accumulation of NORM activity are essentially similar to those for conventional wells, it is anticipated that the concentrations of NORM activity will be comparable to the trends of Th (Thorium) and U (Uranium) activity concentrations in the source rocks from which the connate water is recovered. Figure 1 shows the NORM Origins based on oilfield [16]. Among the many contaminants found in wastewater, sludge, and scales, radium stands out as the most prevalent.…”
Section: Norm In Oilfieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the factors that cause the accumulation of NORM activity are essentially similar to those for conventional wells, it is anticipated that the concentrations of NORM activity will be comparable to the trends of Th (Thorium) and U (Uranium) activity concentrations in the source rocks from which the connate water is recovered. Figure 1 shows the NORM Origins based on oilfield [16]. Among the many contaminants found in wastewater, sludge, and scales, radium stands out as the most prevalent.…”
Section: Norm In Oilfieldmentioning
confidence: 99%
“…Similar exposure may also occur during the decommissioning of facilities used for oil and gas production and waste treatment. The most significant external source of gamma rays for oil workers in the industry derives via the short-lived offspring of 226Ra and 228Ra that exist in scale, sludge, as well as sand [16]. Maximizing distance from source and exposure time are the only ways to minimize such exposure.…”
Section: The Scenarios Of the Norm Exposurementioning
confidence: 99%
“…Despite the Alberta Oil Sands Region being Canada's largest oil mining industry and previous work showing the important contribution of oil and gas activities on the mobilization of NORM in the environment, little research has been done on NORM activity concentrations in wildlife surrounding the AOSR (Koppel et al, 2022;Salahel Din & Rashed, 2021;Salama & Mohmaed, 2021). This project aimed to determine activity concentrations of NORM in the muscles of freshwater fish from areas surrounding the Athabasca oil sands.…”
Section: Discussionmentioning
confidence: 99%
“…NORM is matter found in the natural environment, often in rocks and sand, that contains radioactive elements such as uranium and thorium (World Nuclear Association, 2020). Recent reports have suggested that NORMs may be critical drivers of ecotoxicity in oil and gas-producing regions (Koppel et al, 2022;Salama & Mohmaed, 2021).…”
Section: Constituents Of Potential Concerns (Copcs) In the Aosrmentioning
confidence: 99%